S64 Circulating polymers are found in alpha-1-antitrypsin deficiency and are associated with lung disease. (14th November 2013) - Dickens, JA; Tan, L; DeMeo, DL; Miranda, E; Perez, J; Rashid, ST; Day, J; Ordonez, A; Marciniak, SJ; Haq, I; Barker, AF; Campbell, EJ; et al.
Abstract : Introduction and Objectives: The severe Z deficiency allele of alpha-1-antitrypsin (Glu 342 Lys) results in the formation of polymers that are retained within hepatocytes, leading to hepatitis, cirrhosis and hepatocellular carcinoma. The concomitant lack of circulating protein predisposes to early onset emphysema. Polymers are also found in the lung, skin and kidney and are known to be proinflammatory, but it is unknown whether those polymers are produced locally or are deposited from a circulating source. We wished to establish whether polymers are present in the plasma of individuals with alpha-1-antitrypsin deficiency, from where they originate and whether they are associated with any clinical phenotype. Methods: We used a novel anti-alpha-1-antitrypsin polymer monoclonal antibody (2C1) in an ELISA assay to evaluate whether polymers are present in a cohort of 513 individuals with ZZ alpha-1-antitrypsin deficiency. Serial samples from an individual with ZZ alpha-1-antitrypsin deficiency undergoing liver transplantation were used to investigate the source of circulating polymers. We then used a 2 nd cohort of 293 individuals with mixed alpha-1-antitrypsin phenotypes to determine whether circulating polymers could be used as a screening test for the presence of a polymerogenic allele. Disease associations were sought using clinical data from the ZZ alpha-1-antitrypsin deficient cohort. Results: In the cohort of 513 individuals with PiZZ alpha-1-antitrypsin deficiency, we found 512 had quantifiable polymers present within serum, the 513 th having previously had a liver transplant. Circulating polymer levels were higher in men and individuals with COPD and a there was a correlation with older age and lower lung function. The presence of circulating polymers was 100% sensitive and 89% specific in identifying 20 PiZZ alpha-1-antitrypsin homozygotes in a mix of 293 alpha-1-antitrypsin genotypes. Serial blood samples from a PiZZ individual undergoing liver transplantation showed that circulating polymers originate from the liver, clearing with a half-life of approximately 30 hours and becoming undetectable 5 days after transplantation. Conclusions: We have shown that circulating polymers are present in PiZZ alpha-1-antitrypsin individuals and originate from the liver. Polymer levels are associated with COPD, suggesting they may play a role in disease pathogenesis.